Key factors influencing long-term retention among Contact Centre employee in Malaysia: a Delphi method study - S. Hemmah Subramaniam; Walton Wider; Jem Cloyd M. Tanucan; Kim Yew Lim; Leilei Jiang; Manoch Prompanyo (Cogent Business & Management, 2024)
Attrition is the biggest pain point in the contact-center industry across nations. Hence, it is important to study how to retain contact center employees. This study aimed to identify the key factors influencing long-term retention among contact center employees in Malaysia. The Delphi method was implemented using purposive sampling. A total of 24 experts were selected from the contact center industry, who had been working in the field for more than five years in managerial positions. A two-round Delphi method was conducted where, in the first round, experts were requested to list the factors contributing to long-term retention among contact center employees in Malaysia. Thematic analysis was employed in the first round to identify the dimensions by grouping themes. In the second round, experts were requested to rank the dimensions from the most important to the least important. Based on the findings, the most important factors identified were supportive management, followed by work-life balance, compensation and benefits, working environment, career development, reward and recognition, training and development, and health support. Recommendation was provided to the contact center operation in Malaysia based on this finding on the initiative that can be worked on to retain the contact center employee in Malaysia.
Keywords: 650; contact center; Malaysia; long-term retention; employee; mental health